2021
DOI: 10.1177/1045389x211057218
|View full text |Cite
|
Sign up to set email alerts
|

Production, deformation and magnetorheological characteristics of the alginate/chitosan hydrogel magnetic microspheres

Abstract: To improve dispersion stability and magnetorheological (MR) characteristics of carbonyl iron (CI) particles, we proposed novel hydrogel magnetic microspheres (MPs) dual-coated with alginate (AL) and chitosan (CTS) for the first time. The double-network structures formed by biological crosslinking and chelation reactions are capable to enhance its own structural stability and mechanical properties. The structural characterization, MR properties, and dispersion stability for different MPs were investigated. Addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…In recent years, magnetic resins of chitosan microspheres (MRCM) have attracted increasing attention, owing to their unique magnetic features, good biocompatibility, and low toxicity. For example, some scholars have studied the magnetic microspheres prepared by alginate and chitosan, which have superior magnetorheological characteristics [21]. In addition, a study reported the application of magnetic chitosan microspheres for immobilization of Candida rugosa lipase [22].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, magnetic resins of chitosan microspheres (MRCM) have attracted increasing attention, owing to their unique magnetic features, good biocompatibility, and low toxicity. For example, some scholars have studied the magnetic microspheres prepared by alginate and chitosan, which have superior magnetorheological characteristics [21]. In addition, a study reported the application of magnetic chitosan microspheres for immobilization of Candida rugosa lipase [22].…”
Section: Introductionmentioning
confidence: 99%